Dexmedetomidine improves clinical outcomes in sepsis-induced myocardial injury: a retrospective cohort study - Liu, Yuan; Ouyang, Jianjie; Zhang, Cuicui; Niu, Pingping; Shang, Baoling; Yao, Gengzhen; Shi, Yongyong; Zou, Xu (Frontiers in Pharmacology, 2025)
BackgroundThe efficacy of dexmedetomidine (DEX) in treating sepsis-induced myocardial injury (SIMI) remains unclear. In this study, we explored the relationship between DEX use and clinical outcomes of patients with SIMI, focusing on the dosage and treatment duration.MethodsIn this retrospective cohort analysis, we identified patients with SIMI from the Medical Information Mart for Intensive Care IV (MIMIC-IV) database and categorized them into the DEX and non-DEX groups based on intensive care unit treatment. The baseline bias was reduced through propensity score matching (PSM). The primary outcome was 28-day mortality, whereas the secondary outcomes were in-hospital mortality and mortality rates at 7 days, 90 days, and 1 year. The association between DEX use and in-hospital mortality was assessed using Kaplan–Meier analysis and Cox proportional hazards models.ResultsAfter PSM, 373 patients in the DEX group were matched with 579 patients in the non-DEX group to achieve a balanced distribution of the covariates. The Cox regression model demonstrated a significant reduction in the 28-day mortality associated with DEX use, yielding a hazard ratio (HR) of 0.61 (95% confidence interval [CI]: 0.47–0.78, P < 0.001). In-hospital mortality also significantly decreased (HR = 0.43, 95% CI: 0.33–0.57, P < 0.001). Lower mortality rates were observed at 7 days, 90 days, and 1 year. DEX doses >0.4 μg/kg/h, particularly in the range of 0.400–0.612 μg/kg/h, total doses >3.113 mg during hospitalization, and treatment durations exceeding 72 h were associated with improved mortality risk at all intervals. Regarding DEX efficacy at 28 days, our subgroup analyses indicated a significant interaction between the Sequential Organ Failure Assessment score and invasive mechanical ventilation.ConclusionDEX administration was associated with improved in-hospital mortality and reduced mortality rates at 7 days, 28 days, 90 days, and 1 year in patients with SIMI. These findings require validation in future studies.